Maxims in Novel “The Fault in Our Stars” by John Green: Pragmatics Approach - Sasmi Saragih; Mhd Johan (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2020)
This research aimed at analyzing the types of maxims of the cooperative principle that were used in the novel entitled The Fault in Our Stars. The data source of data was a novel entitled The Fault in Our Stars that fulfilled cooperative principle based on four maxims of cooperative principles: Maxim of quantity, maxim of quality, maxim of relation, and maxim of manner. Theory that the researcher used in this research was theory of Grice. In this research, a descriptive qualitative method was applied to answer the research questions. The observational method and non-participatory technique were applied by the researcher in collecting the data. In analyzing the data the researcher used pragmatic identity method based on the theory of Sudaryanto. The results showed that the level of cooperative principle was mostly used in the novel. The researcher found 30 data related to cooperative principle. The maxims of quantity have 15 data, 3 for maxim of quality, 10 for maxim of relation and maxim of manner has only 2 data.